Survival Analysis Of COVID-19 Patients With Type 2 Diabetes: Lesson From Pandemic - Nadia Putri; Asri C. Adisasmita (Jurnal Dunia Kesmas, 2026)
Type 2 diabetes mellitus (T2DM) is a common chronic comorbidity that exacerbates the clinical course of COVID-19, leading to higher complication rates and mortality. Patients with T2DM experience impaired immunity, persistent inflammation, and metabolic dysfunction, making them more vulnerable to severe viral infections. Despite extensive global research, evidence from Indonesia remains scarce, highlighting the need for local data to guide public health strategies. This study aimed to analyze the survival of COVID-19 patients with T2DM and identify factors associated with mortality in Padang City. A retrospective cohort study using surveillance data from the Padang City Health Office between March 2020 and March 2021 included 209 randomly selected patients. Survival analysis was conducted using Kaplan–Meier methods, and Cox regression models identified mortality predictors. The study found that 6.7% of patients died, with an incidence rate of 0.0058. T2DM patients had nearly four times the risk of death compared to non-diabetic individuals (HR = 3.9; 95% CI: 1.2–14.2). Other predictors included older age, male sex, multiple comorbidities, symptomatic status, and hospitalization. These findings emphasize the need to prioritize T2DM patients in vaccination, early detection, and integrated diabetes management to strengthen health system resilience.